2019
DOI: 10.5455/javar.2019.f333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wound healing potential of pomegranate (Punica granatum) whole fruit extract on skin burn wound in rats (Rattus norvegicus)

Abstract: Objective: This research was conducted to study the wound healing process of whole fruit pomegranate extract ( punica granatum ) standardized with 40% ellagic acid ointment for deep second-degree burn wound of skin in the rat ( Rattus norvegicus ). Materials and Methods: Powder of standardized pomegranate extract (SPE) with 40% ellagic acid was processed to become ointments. Twenty-five male rats, weighed 150–180 gm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…The most frequently exploited plant material for In Vivo studies was the peel from fruit, extracted by maceration with combined polar solvents like ethanol:water or methanol:water, namely more organic solvent than water (at least a ratio of 70:30). Lukiswanto et al [ 52 ] and Yuniarti et al [ 53 ] obtained the healing activity, respectively, in the models of hot plate-induced burn and linear incision, with similar concentrations of corresponding ellagic acid (4% and 3% of the ointment, about 20–15 mg/kg referring to 0.5 g of topical application). Mo et al [ 54 ] paralleled the effect of pomegranate peel extract (5%) and the relative amount of pure ellagic acid (0.65%, close to 3.25 mg/kg) on excision, incision, and burn model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently exploited plant material for In Vivo studies was the peel from fruit, extracted by maceration with combined polar solvents like ethanol:water or methanol:water, namely more organic solvent than water (at least a ratio of 70:30). Lukiswanto et al [ 52 ] and Yuniarti et al [ 53 ] obtained the healing activity, respectively, in the models of hot plate-induced burn and linear incision, with similar concentrations of corresponding ellagic acid (4% and 3% of the ointment, about 20–15 mg/kg referring to 0.5 g of topical application). Mo et al [ 54 ] paralleled the effect of pomegranate peel extract (5%) and the relative amount of pure ellagic acid (0.65%, close to 3.25 mg/kg) on excision, incision, and burn model.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action was partially explained—despite the analogue use of whole fruit extracts, standardized on ellagic acid amount (40%), Lukiswanto et al [ 52 ] and Yuniarti et al [ 53 ] observed the increase in collagen deposition but also divergent effects on polymorphonuclear (PMN) cells infiltration and angiogenesis. However, Mo et al [ 54 ] attributed the increase in hydroxyproline content and collagen deposition to the extract, but not to ellagic acid; granulation and inflammation were absent in the treated tissue, even when ellagic acid was used alone, thus supporting the observations of Lukiswanto et al [ 52 ] about impaired angiogenesis and PMN infiltration. In addition to the anti-inflammatory activity, ellagic acid (0.65%) counteracts the expression of myeloperoxidase in damaged tissue (−53%), leading to antioxidant activity [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of its folklore medicinal status, crude pomegranate extracts and its constituent compounds, such as punicalagin, have received much biomedical attention given the considerable evidence supporting their efficacy against a wide range of diseases and conditions, ascribed to its various anticancer, antimicrobial, anti-inflammatory and antioxidant bioactivities [ 16 ]. Although numerous studies have previously endorsed the beneficial effects of PRE and punicalagin and advocated their application in the treatment of impaired wound healing responses in skin [ 19 , 20 , 21 , 22 , 23 , 24 ], a clinical area which has largely been overlook from a wound healing viewpoint are the potential abilities of PRE and punicalagin within the oral cavity, when tissue damage is commonly caused by periodontal disease and trauma. Indeed, periodontal diseases, comprising gingivitis and periodontitis, are regarded as being the most common disease of mankind, leading to huge economic burdens for healthcare providers worldwide [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fruit exocarp (rind) is particularly abundant in hydrolysable tannins, in particular punicalagin, which is a large (mw 1,084.71 g/mol) molecule comprised of gallagic acid and ellagic acid linked via a glucose moiety ( Figure 1 ) [ 18 , 19 ]. These compounds have been attributed as being the primary sources of bioactivity responsible for the desirable medicinal properties of pomegranate, including their dermal wound healing efficacies [ 19 , 20 , 21 , 22 , 23 , 24 ]. Indeed, from our previous work, pomegranate rind extract (PRE) and punicalagin itself have been shown to exhibit potent anti-inflammatory, antimicrobial and antiviral activities, which can be further potentiated by combination with Zn (II) ions [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%